Fornical Closed-Loop Stimulation for Alzheimer's Disease. Issue 7 (July 2018) - Senova, Suhan; Chaillet, Antoine; Lozano, Andres M.
Abstract : Pharmacological neuromodulation strategies have shown limited efficacy in treating memory deficits related to Alzheimer's disease (AD). Despite encouraging results from a few preclinical studies, clinical trials investigating open-loop deep brain stimulation (DBS) for AD have not been successful. Recent refinements in understanding the various phases of memory processes, animal studies investigating phase-specific modulation of hippocampal activity during memorization, and clinical studies using closed-loop DBS strategies to treat patients with movement disorders, all point to the need to investigate closed-loop fornical DBS strategies to better understand memory dynamics and potentially treat memory deficits in AD preclinical models. Highlights: Dysfunction of synapses and brain oscillations within the Papez circuit may be crucial in AD. Open-loop DBS of the fornix activates robustly the Papez circuit, but does not translate into significant alleviation of memory deficits in patients with AD. The timing and rhythmicity of neuromodulation by DBS may be crucial for a more physiologically relevant functional activation of memory circuits and better clinical outcomes.